The History Of Gender In Central Asia And Contemporary Issues (Texas Journal of Multidisciplinary Studies, 2024)
The article analyzes the historical evolution of gender roles in the region and their current significance and importance. It examines how gender policies and social changes unfolded during the Soviet era and post-independence periods, highlighting the persistence of traditional-patriarchal systems and their impact on modern society. Additionally, the article delves into issues of gender equality in contemporary Central Asian societies, the provision of equal opportunities for men and women in education and workplaces, and the acceptance of gender stereotypes. The research is based on modern academic literature, aiming to identify existing gender issues in the region and provide recommendations for their resolution.